2018
DOI: 10.1101/474700
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reporters of TCR signaling identify arthritogenic T cells in murine and human autoimmune arthritis

Abstract: How pathogenic CD4 T cells in Rheumatoid Arthritis (RA) develop remains poorly understood.We used Nur77-a marker of T cell antigen receptor (TCR) signaling-to identify antigenactivated CD4 T cells in the SKG mouse model of autoimmune arthritis and in patients with RA.Using a fluorescent reporter of Nur77 expression in SKG mice, we found that higher levels of Nur77-eGFP in SKG CD4 T cells marked their autoreactivity, arthritogenic potential, and ability to more readily differentiate into IL-17 producing cells. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(47 citation statements)
references
References 90 publications
(125 reference statements)
5
42
0
Order By: Relevance
“…showed that low concentrations of anti‐CD3 antibody (~0·5 µg/ml) together with IL‐2 and TGF‐β promoted Treg differentiation, while high concentrations (~5 µg/ml) rather suppressed Foxp3 expression and induced Th17 differentiation . Ashouri et al . used Nur77‐GFP reporter in an arthritis‐prone background and showed that Nur77‐GFP high cells are enriched with arthritogenic Th17 cells.…”
Section: Roles Of Bivalent Foxp3‐containing Transcription Factor Compmentioning
confidence: 99%
“…showed that low concentrations of anti‐CD3 antibody (~0·5 µg/ml) together with IL‐2 and TGF‐β promoted Treg differentiation, while high concentrations (~5 µg/ml) rather suppressed Foxp3 expression and induced Th17 differentiation . Ashouri et al . used Nur77‐GFP reporter in an arthritis‐prone background and showed that Nur77‐GFP high cells are enriched with arthritogenic Th17 cells.…”
Section: Roles Of Bivalent Foxp3‐containing Transcription Factor Compmentioning
confidence: 99%
“…In in vitro autologous mixed lymphocyte reaction (AMLR), self‐reactive SKG CD4SP mature thymocytes, and CD4 + T cells actively proliferated in response to self‐peptides/MHC complexes on APCs, whereas BALB/c WT CD4SP thymocytes or CD4 + T cells were scarcely responsive . Supporting these findings, GFP high , that is, highly self‐reactive, T cells in SKGNur mice described above were prone to differentiate in vivo into Th17 cells with arthritogenicity, and proliferated more robustly in AMLR compared with WTNur mice . Such AMLR also revealed that IL‐6 was predominantly produced by APCs, TNF‐α by both APCs and T cells, while IL‐17 was produced only by effector CD4 + T cells but not by CD4SP thymocytes .…”
Section: Th17 Cell–dependent Chronic Autoimmune Arthritismentioning
confidence: 72%
“…Regardless of hyporesponsiveness to TCR stimulation due to Zap70 skg mutation, SKG mice harbor phenotypically activated CD4 + T cells presumably because of their high self‐reactivity. A recent study using Nur77 ( NR4a1 )‐eGFP as a reporter for TCR signaling strength in SKG and WT mice (SKGNur and WTNur mice, respectively) indeed demonstrated that self‐reactivity and arthritogenicity of peripheral CD4 + T cells were well correlated with the levels of Nur77 expression . For example, SKGNur mice had an increased number of CD44 high CD62L low effector/memory CD4 + T cells enriched in the GFP high population, which was also high in the arthritogenicity; adoptive transfer of GFP high T cells into severe combined immunodeficiency (SCID) mice induced early‐onset severe arthritis, in contrast with late‐onset milder arthritis by GFP low T cell transfer.…”
Section: Autoimmunity Caused By Impaired Tcr‐proximal Signalingmentioning
confidence: 99%
“…Strikingly, up to 30% of CD4 + Tconv and slightly fewer CD8 + T cells in fetal skin were CD45RO + (Figures 3A-3C). Higher levels of Nur77, a specific reporter of T cell receptor (TCR) signaling, [27][28][29] were detected in fetal CD45RO + versus CD45RA + cells, further suggesting antigen stimulation in this putative memory population (Figures 3D-3F).…”
Section: Mass Cytometry Elucidates Major Immune Cell Subsets In Human Fetal Skinmentioning
confidence: 95%